Association of the tumour necrosis factor α −308 but not the interleukin 10 −627 promoter polymorphism with genetic susceptibility to primary sclerosing cholangitis - Mitchell, S (2001)
BACKGROUND AND AIMS—Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease of unknown aetiology. Abnormalities in immune regulation and genetic associations suggest that PSC is an immune mediated disease. Several polymorphisms within the tumour necrosis factor α (TNF-α) and interleukin 10 (IL-10) promoter genes have been described which influence expression of these cytokines. This study examines the possible association between polymorphisms at the −308 and −627 positions in the TNF-α and IL-10 promoter genes, respectively, and susceptibility to PSC. METHODS—TNF-α −308 genotypes were studied by polymerase chain reaction (PCR) in 160 PSC patients from Norway and the UK compared with 145 ethnically matched controls. IL-10 −627 genotypes were studied by PCR in 90 PSC patients compared with 84 ethnically matched controls. RESULTS—A total of 16% of Norwegian PSC patients and 12% of British PSC patients were homozygous for the TNF2 allele compared with 3% and 6% of respective controls. The TNF2 allele was present in 60% of PSC patients versus 30% of controls (OR(combined data)=3.2 (95% confidence intervals (CI) 1.8-4.5); p(corr)=10(−5)). The association between the TNF2 allele and susceptibility to PSC was independent of the presence of concurrent inflammatory bowel disease (IBD) in the PSC patients; 61% of PSC patients without IBD had TNF2 compared with 30% of controls (OR(combined data)=3.2 (95% CI 1.2-9.0); p(corr)=0.006 ). There was no difference in the −627 IL-10 polymorphism distributions between patients and controls in either population. The increase in TNF2 allele in PSC patients only occurs in the presence of DRB1*0301 (DR3) and B8. In the combined population data, DRB1*0301 showed a stronger association with susceptibility to PSC than both the TNF2 and B8 alleles (OR(combined data)=3.8, p(corr)=10(−6) v OR(combined data)=3.2, p(corr)=10(−5) v OR(combined data )=3.41, p(corr)=10(−4), respectively). CONCLUSIONS—This study identified a significant association between possession of the TNF2 allele, a G→A substitution at position −308 in the TNF-α promoter, and susceptibility to PSC. This association was secondary to the association of PSC with the A1-B8-DRB1*0301-DQA1*0501-DQB1*0201 haplotype. No association was found between the IL-10 −627 promoter polymorphism and PSC.   Keywords: primary sclerosing cholangitis; tumour necrosis factor; interleukin 10; genetic polymorphism